Professionalism: a holistic training widely neglected among medical professionals of Pakistan - Ateeque, Kanza; Jamal, Maira; Zafar Sayeed, Bushra (Journal of the Pakistan Medical Association, 2022)
Abstract not required as this is a letter to the editor